pH in the plant endomembrane system: an import and export business - Schumacher, Karin (Current opinion in plant biology, 2014)
pH homeostasis is an essential process in all plant cells and the maintenance of correct luminal pH in the compartments of the endomembrane system is important not only for secondary active transport but also for a variety of cellular functions including protein modification, sorting, and trafficking. Due to their electrogenicity primary H+-pumps cannot establish and control the often large proton-gradients single-handedly but require the co-action of other ion transporters that serve as either shunt conductances or proton-leaks. Here, I will thus focus on recent results that highlight the interplay of proton-pumps and proton-coupled transporters in controlling pH in the compartments of the plant endomembrane system.